Socialism goes global the Soviet Union and Eastern Europe in the age of decolonisation - Mark, James 1972-; Betts, Paul 1963- (Oxford University Press, 2022)
'Socialism Goes Global' provides a broad history of the relationship between Eastern Europe and the decolonising world ranging from the nineteenth to the late twentieth century. At its core is the post-1945 period, when socialism's importance as a globalising force accelerated and drew together what contemporaries called the 'Second' and 'Third Worlds'